2016
DOI: 10.1177/0163278716674247
|View full text |Cite
|
Sign up to set email alerts
|

A Factor Analytic Investigation of the Person-in-Recovery and Provider Versions of the Revised Recovery Self-Assessment (RSA-R)

Abstract: Recovery is understood as living a life with hope, purpose, autonomy, productivity, and community engagement despite a mental illness. The aim of this study was to provide further information on the psychometric properties of the Person-in-Recovery and Provider versions of the Revised Recovery Self-Assessment (RSA-R), a widely used measure of recovery orientation. Data from 654 individuals were analyzed, 519 of whom were treatment providers (63.6% female), while 135 were inpatients (10.4% female) of a Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…It is a self-reflective tool that is designed to identify efforts made by healthcare agencies to provided recovery-oriented care. Research has shown that the RSA has moderate to strong internal reliability (Cronbach’s α 0.63–0.90) [ 38 41 ]. Response options include a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree) and two additional answering options (Don’t know and Not Applicable) [ 42 ].…”
Section: Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a self-reflective tool that is designed to identify efforts made by healthcare agencies to provided recovery-oriented care. Research has shown that the RSA has moderate to strong internal reliability (Cronbach’s α 0.63–0.90) [ 38 41 ]. Response options include a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree) and two additional answering options (Don’t know and Not Applicable) [ 42 ].…”
Section: Methods and Designmentioning
confidence: 99%
“…The Choice domain indicates to what degree healthcare provider and clients feel that choices are available to clients and if the choice is respected. The subscale Individually Tailored Services refers to the perception that healthcare services are tailored to individuals’ personal needs, culture and affectations [ 41 ]. Higher scores indicate a greater degree of implementation of recovery-oriented practices [ 38 ].…”
Section: Methods and Designmentioning
confidence: 99%
“…It is a self-re ective tool that is designed to identify efforts made by healthcare agencies to provided recovery-oriented care. Research has shown that the RSA has moderate to strong internal reliability (Cronbach's α 0.63 -0.90) (24)(25)(26)(27). Response options include a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree) and two additional answering options (Don't know and Not Applicable) (28) Adjust Treatment if Patients are not responding, and other tasks Important for our Program.…”
Section: Recovery Self-assessment (Rsa-provider Version)mentioning
confidence: 99%
“…The RSA has shown very good internal consistency in similar research environments (alpha = 0.96). Higher scores indicate that staff feel their workplace has a greater implementation of recovery-oriented practices [46,47].…”
Section: • Intervention Fidelitymentioning
confidence: 99%